Brucella ceti Infection in Harbor Porpoise (Phocoena phocoena) - Thierry P. Jauniaux; Cecile Brenez; David Fretin; Jacques Godfroid; Jan Haelters; Thierry Jacques; Francis Kerckhof; Jan Mast; Michael Sarlet; Freddy L. Coignoul (Emerging Infectious Diseases, 2010)
We describe Brucella sp. infection and associated lesions in a harbor porpoise (Phocoena phocoena) found on the coast of Belgium. The infection was diagnosed by immunohistochemistry, transmission electron microscopy, and bacteriology, and the organism was identified as B. ceti. The infection’s location in the porpoise raises questions of abortion and zoonotic risks.